ZmBAK1 confers maize resistance to Gibberella stalk rot caused by Fusarium graminearum via activating PAMP-triggered immunity - Fugui Xie; Yali Sun; Huilan Zhang; Junjie Cui; Qing Wang; Xiquan Gao (Plant Signaling & Behavior)
Gibberella stalk rot (GSR) caused by Fusarium graminearum is one of the most devastating diseases of maize, not only seriously affecting its yield and the application of mechanized harvest technology but also producing a variety of toxins, thus seriously impacting the food safety. BAK1 (Brassinosteroid-Insensitive 1-Associated Receptor Kinase 1, BAK1) is the well-studied co-receptor of PRRs (Pattern Recognition Receptors), which is involved in the regulation of growth and development regulation as well as the response to diverse biological stresses. However, little is known about the role of BAK1 in the interaction between maize and pathogens, especially in maize against GSR. In this study, we found that ZmBAK1 (Zm00001d037297) was located at the cytoplasmic membrane. Furthermore, ZmBAK1 was induced by multiple PAMPs (Pathogen-Associated Molecular Patterns), while PTI (PAMP-Triggered Immunity) response including ROS (Reactive Oxygen Species) burst and callose deposition, as well as cell death, and immune gene expression was weakened in bak1 mutant upon PAMP treatment. On the contrary, the ROS production and cell death in BAK1-OE were significantly stronger than wild type. Furthermore, bak1 mutant is more susceptible to GSR, while BAK1-OE is more resistant, compared to wild types. Taken together, our data suggested that ZmBAK1 plays a positive role in maize GSR resistance, likely via activating PTI signaling pathway.